1998
DOI: 10.1002/(sici)1521-4109(199807)10:9<638::aid-elan638>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Voltammetry of Two Analogue K-Group Vitamin Compounds in Dimethylsulfoxide

Abstract: The electrochemical reduction of two analogue K-group vitamin compounds, menadione and phthiocol, was studied by cyclic voltammetry in DMSO on glassy carbon electrodes. The reduction process of the more biologically active of these compounds (menadione), is associated with the formation of the semiquinone anion radical and the dianion. Two separated reversible one-electron peaks were observed. In contrast, the less biologically active phthiocol exhibits a single irreversible 2/3-electron peak which is explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…It is noticeable that upon the addition of base, a considerable amount of water is now present during the experiments (the TBAOH used is a 1 M aqueous solution). The stability of the ESR signals confirms that the added water behaves as a very weak proton donor in acetonitrile, as was previously described for DMSO [17].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…It is noticeable that upon the addition of base, a considerable amount of water is now present during the experiments (the TBAOH used is a 1 M aqueous solution). The stability of the ESR signals confirms that the added water behaves as a very weak proton donor in acetonitrile, as was previously described for DMSO [17].…”
Section: Resultssupporting
confidence: 84%
“…Some authors propose that the reduction proceeds by a monoelectronic reduction of Q-O À , (Eq. (6)) [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…NQ is the reference quinone for this study [27,28]. In the particular case of the a-phenolic-naphthoquinones HNQ and H 2 NQ, it is observed that the chemical reversibility of the voltammetric waves is not lost by the effect of the presence of the a-phenolic groups, which allows us to discard the intervention of any self-protonation reaction [29,30]. Contrasting with this, the weak acidity of the a-phenolic protons accounts for the intervention of non-covalent interactions which provokes important differences in the redox potentials and current intensities.…”
Section: Instrumentation and Electrodesmentioning
confidence: 99%
“…There is a controversy about the identification of the electrochemical process associated with the reduction of the conjugated base of the a-hydroxy quinones [22,32,44,49]. The in situ electronic spin resonance (ESR) results of the electrolysis of these quinones at the applied potential corresponding to the anion reduction process support a monoelectronic transfer in the reduction [50].…”
Section: Influence Of the Internal Proton Donormentioning
confidence: 99%